Altered effective connectivity of resting state networks by acupuncture stimulation in stroke patients with left hemiplegia: A multivariate granger analysis. Issue 47 (November 2017) - Fu, Cai-Hong; Li, Kuang-Shi; Ning, Yan-Zhe; Tan, Zhong-Jian; Zhang, Yong; Liu, Hong-Wei; Han, Xiao; Zou, Yi-Huai
Abstract : Abstract: The aim of this study was to explore the response feature of resting-state networks (RSNs) of stroke patients with left hemiplegia by acupuncture stimulation. Nineteen stroke patients with left hemiplegia and 17 controls were recruited in this study. Resting-state functional magnetic resonance imaging data before and after acupuncture were acquired using magnetic scanning. The independent component analysis (ICA) was employed to extract RSNs related to motion, sensation, cognition, and execution, including sensorimotor network (SMN), left and right frontoparietal network (LFPN and RFPN), anterior and posterior default mode network (aDMN, pDMN), visual network (VN), and salience network (SN). Granger causality method was used to explore how acupuncture stimulation affects the causality between intrinsic RSNs in stroke patients. Compared with healthy subjects, stroke patients presented the more complex effective connectivity. Before acupuncture stimulation, LFPN inputted most information from other networks while DMN outputted most information to other networks; however, the above results were reversal by acupuncture. In addition, we found aDMN reside in between SMN and LFPN after acupuncture. The finding suggested that acupuncture probably integrated the effective connectivity internetwork by modulating multiple networks and transferring information between LFPN and SMN by DMN as the relay station. Abstract : Supplemental Digital Content is available in the text